2021
DOI: 10.3389/fvets.2021.709737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FecB Mutation on Estrus, Ovulation, and Endocrine Characteristics in Small Tail Han Sheep

Abstract: The Booroola fecundity gene (FecB) has a mutation that was found to increase the ovulation rate and litter size in Booroola Merino sheep. This mutation is also associated with the fecundity of small-tail han (STH) sheep, an important maternal breed used to produce hybrid offspring for mutton production in China. Previous research showed that the FecB gene affects reproduction in STH sheep, based on litter size records. However, the effects of this gene on estrus, ovulation, and endocrine characteristics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
2
26
1
Order By: Relevance
“…Firstly, ewes were treated with vaginal sponges (300 mg progesterone; InterAg Co., Ltd., Hamilton, New Zealand), followed by injection of vitamin AD to protect the endometrium. The vaginal sponges were evacuated after 12 days, and the removal time was set as 0 h. In accordance with previous reproductive trait analyses, six ewes (three BB and three WW ewes) were euthanized at 45 h (follicular phase) and six ewes (three BB and three WW ewes) at 216 h (luteal phase) ( 30 , 31 ). Pituitary samples were dissected immediately after euthanasia, frozen in liquid nitrogen, and stored at −80°C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, ewes were treated with vaginal sponges (300 mg progesterone; InterAg Co., Ltd., Hamilton, New Zealand), followed by injection of vitamin AD to protect the endometrium. The vaginal sponges were evacuated after 12 days, and the removal time was set as 0 h. In accordance with previous reproductive trait analyses, six ewes (three BB and three WW ewes) were euthanized at 45 h (follicular phase) and six ewes (three BB and three WW ewes) at 216 h (luteal phase) ( 30 , 31 ). Pituitary samples were dissected immediately after euthanasia, frozen in liquid nitrogen, and stored at −80°C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Fec B is a major effect gene associated with the lambing number trait in sheep, which has been used as a crucial molecular marker for selecting high-fertility sheep. [1][2][3][4][5][6] Studies have shown that Fec B has an additive effect on the ovulation rate, with effects on litter size ranging from additive to dominant depending on the genotype. 7 However, the molecular mechanism of Fec B mutation in the regulation of lambing number traits in sheep remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of lambs produced by sheep is fundamental to the availability of sheep products. Fec B is a major effect gene associated with the lambing number trait in sheep, which has been used as a crucial molecular marker for selecting high‐fertility sheep 1–6 . Studies have shown that Fec B has an additive effect on the ovulation rate, with effects on litter size ranging from additive to dominant depending on the genotype 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The Booroola fecundity gene ( Fec B ), also known as the bone morphogenetic protein receptor-1B (BMPR1B) gene, is the first major gene discovered that is related to sheep fertility [ 1 , 2 , 3 , 4 , 5 ]. Fec B is also involved in granulosa cell differentiation, follicle development, and ovulation in sheep [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%